COVID-19 and Obesity: Epidemiology, Pathogenesis and Treatment - Zhu X; Yang L; Huang K (Diabetes, Metabolic Syndrome and Obesity, 2020)
Xinyu Zhu,1,2,* Liu Yang,1,2,* Kai Huang1,2 1Department of Cardiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China; 2Clinical Center for Human Genomic Research, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Kai HuangDepartment of Cardiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, 1277 Jiefang Ave, Wuhan, Hubei 430022, People’s Republic of ChinaEmail Husthuang1003@163.comAbstract: The growing prevalence of overweight and obesity has been a worldwide public health issue. During the COVID-19 pandemic, obesity is associated with a higher risk of severity and a worse clinical outcome of SARS-COV-2 infection. This may be because of the chronic low-grade inflammation, impaired immune response and metabolic disorders in obese patients. In this narrative review, we have summarized the association between obesity and COVID-19 and discussed the potential pathogenesis and treatment in these patients. This work may provide practical suggestions on the clinical management of obese COVID-19 patients.Keywords: COVID-19, obesity, SARS-COV-2